Transsphenoidal Surgery of Giant Pituitary Adenoma: Results and Experience of 239 Cases in A Single Center - Chen, Yike; Xu, Xiaohui; Cao, Jing; Jie, Yuanqing; Wang, Linkai; Cai, Feng; Chen, Sheng; Yan, Wei; Hong, Yuan; Zhang, Jianmin; Wu, Qun (Frontiers in Endocrinology, 2022)
Background: Transsphenoidal surgery (TSS) is first-line treatment for giant pituitary adenomas (PAs). Although PA is a benign neuroendocrine tumor that originates from adenohypophysial cells, the surgical outcomes and prognosis of giant PAs differ significantly due to multiple factors such as tumor morphology, invasion site, pathological characteristics and so on. The aim of this study was to evaluate surgical outcomes of giant PAs in a single-center cohort. Methods: The clinical features and outcomes of 239 patients with giant PA who underwent sphenoidal surgery at the Second Affiliated Hospital of Zhejiang University School of Medicine from January 2015 to October 2021 were collected from medical records. The basic clinical information (age, gender, function etc.), surgical procedure, imaging features (maximum diameter, invasion characteristics, tumor shape etc.) and histopathological characteristics (pathological results, Ki-67, P53 etc.) were retrospectively reviewed. SPSS 25.0 and Stata 12.0 software were used for statistical analysis. Results: A total of 239 patients with giant PAs underwent TSS, of which 168 surgeries (70.29%) were endoscopic endonasal transsphenoidal (EETS) and 71 (29.71%) were microscopic transsphenoidal (MTS). The mean preoperative maximum diameter in the cohort was 45.64 mm. Gross-total resection was achieved in 46 patients (19.25%), near-total in 56 (23.43%), subtotal in 68 (28.45%), and partial in 69 (28.87%) patients. The maximum tumor diameter and Knosp grade were the significant factors that limited the extent of the resection of giant PAs. A total of 193 patients (80.75%) experienced surgical complications, and the most common complications were postoperative diabetes insipidus (DI) (91, 38.08%), intracranial infection (36, 15.06%) and cerebrospinal fluid (CSF) leaks (37, 15.48%). In addition, there was a significant difference in the incidence of CSF leaks between the neuroendoscopy group and the microscopic group (P < 0.05). Conclusion: The management of giant PAs remains a therapeutic challenge due to their large size and postoperative complications. The maximum diameter and Knosp grade of giant PAs significantly limited the extent of resection, which warrants a reasonable surgical plan.